1989
DOI: 10.1056/nejm198910263211705
|View full text |Cite
|
Sign up to set email alerts
|

Increased Preoperative Collection of Autologous Blood with Recombinant Human Erythropoietin Therapy

Abstract: To study whether the administration of recombinant human erythropoietin increases the amount of autologous blood that can be collected before surgery, we conducted a randomized, controlled trial of erythropoietin in 47 adults scheduled for elective orthopedic procedures. The patients received either erythropoietin (600 units per kilogram of body weight) or placebo intravenously twice a week for 21 days, during which time up to 6 units of blood was collected. Patients were excluded from donation when their hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
134
0
16

Year Published

1991
1991
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 484 publications
(154 citation statements)
references
References 14 publications
1
134
0
16
Order By: Relevance
“…The application of exogenous recombinant human EPO has been shown to accelerate the recovery of red cell volume in phlebotomized animals 12 as well as in autologous blood donors. 13 Its use in healthy persons, however, is still hampered by the facts that not all side effects of the recombinant hormone may yet be known and that the reported side effects 44,45 are not completely understood in regard to their causal mechanisms. If these concerns are overcome with increased experience in the treatment of chronic anemia with recombinant human EPO, its use may acquire a place in preoperative autologous blood donation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of exogenous recombinant human EPO has been shown to accelerate the recovery of red cell volume in phlebotomized animals 12 as well as in autologous blood donors. 13 Its use in healthy persons, however, is still hampered by the facts that not all side effects of the recombinant hormone may yet be known and that the reported side effects 44,45 are not completely understood in regard to their causal mechanisms. If these concerns are overcome with increased experience in the treatment of chronic anemia with recombinant human EPO, its use may acquire a place in preoperative autologous blood donation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, recombinant human EPO may be administered, a treatment that is effective in the management of the anemia that occurs with renal failure and has recently been shown to allow the withdrawal of larger amounts of blood from animals who are phlebotomized repeatedly 12 and from autologous blood donors. 13 To obtain a rational basis for such preoperative donation strategies, knowledge of the pattern of variations in endogenous EPO concentration following repeated phlebotomy would be helpful. A recent study 14 suggested only slight increases during preoperative deposit.…”
mentioning
confidence: 99%
“…Recommended dosage in these patients is 600 IU/kg (or a 40,000 IU vial), twice a week during the period that blood is being collected [5,22,23,24,30,41,74,82]. Again, when haemoglobin reaches levels above 15 g/dl, the dose is not administered.…”
Section: Dosingmentioning
confidence: 99%
“…Nevertheless, ABD may involve certain problems inherent to the process, such as anaemia or adverse reactions on the part of the patient during donation, wastage of blood units due to delayed surgery, or clerical errors in blood labelling and storage [1,4,38,74,84]. Moreover, in certain circumstances it may be difficult to collect sufficient blood to cover the estimated loss during surgery [7,17,41,43,48,70].…”
Section: Role Of Rhuepo In Preoperative Autologous Blood Donationmentioning
confidence: 99%
See 1 more Smart Citation